Hubungan Kepatuhan Pengobatan Pasien TB Paru terhadap Hasil Pemeriksaan BTA di Puskesmas Cicangkal Kabupaten Bogor - Syeilla Hana Astria; Ira Gustira Rahayu; Sulaeman .; Sonny Feisal Rinaldy (CV. ITTC INDONESIA, 2026)
Pulmonary tuberculosis (TB) remains a major public health challenge in Indonesia, the country with the second-highest TB burden in the world after India. Successful eradication of Mycobacterium tuberculosis from the patient's body largely depends on consistent adherence to Anti-Tuberculosis Drug (ATD) regimens for a minimum of six months. This study aimed to determine the relationship between treatment adherence among pulmonary TB patients and Acid-Fast Bacilli (AFB) examination results at Cicangkal Primary Health Center, Bogor Regency. An observational analytic design with a cross-sectional approach was applied. A total of 32 pulmonary TB patients who had completed treatment were enrolled using a total sampling technique. Adherence data were obtained from TB registers, Treatment Supervisor (PMO) records, and 30-day medication adherence logs, while AFB results were obtained from laboratory records at the end of therapy. Data were analyzed univariately and bivariately using Fisher's Exact Test. The results showed that 29 respondents (90.6%) were adherent and 3 respondents (9.4%) were non-adherent. Twenty-seven respondents (84.4%) had negative AFB results, whereas 5 respondents (15.6%) remained positive. Statistical testing yielded a p-value of 0.002 (p<0.05), indicating a significant relationship between treatment adherence and AFB results. Higher adherence was associated with a greater likelihood of achieving AFB conversion to negative at the end of treatment. Strengthening the role of PMO, continuous education, and nutritional monitoring are recommended to support successful TB treatment at the primary care level.